DETERMINATION OF NUTRIENTS AND ANTI-NUTRIENTS CONTENTS OF Sorghum bicolor and Glycine max - SIDDAN, A. A.; ABUBAKAR, S. M.; A. M. GADANYA; A. S. YAHAYA; D. MUHAMMAD; F. U. MAIGARI (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
Increasing consumption of Sorghum bicolor and Glycine max in most part of Northern Nigeria exists because of their acclaimed health benefit of treating malnutrition in children. However, there are nutritional disadvantage of their too much consumption. This study investigated the proximate, minerals, vitamins, amino acid composition, and phytochemicals of Sorghum bicolor and Glycine max. The parameters evaluated were moisture contents; ash contents; crude protein; crude lipids; crude fiber; carbohydrates; mineral ions; vitamins; amino acids and phytochemicals. The results obtained showed that all the proximate parameters, minerals; sodium, calcium and vitamins A, C, E and phytochemicals contents in the two samples are significantly difference at p<0.05. No significant different difference (p<0.05) was observed in the amount of magnesium, potassium and iron. Copper was not detected in Sorghum bicolor while tannin was not detected in Glycine max. Eighteen amino acids were detected in both the S. bicolor and G. max. Phytochemicals including saponins, glycosides, alkaloids, oxalates, and phytates were present at moderately higher concentrations in S. bicolor while tannins, steroids, and flavonoids were present in the samples. Sorghum plays an important role in the diet which serves as a major source of carbohydrate in both human and livestock diet for release of energy needed for normal body metabolism, while soy foods are also good sources of dietary fibre, B-vitamins, calcium, and omega-3 essential fatty acids. This work revealed that S. bicolor and G. max can be considered as good sources of carbohydrates, mineral and amino acids.